PENYULUHAN TENTANG PEMBUATAN KRIPIK DARI BONGGOL PISANG PADA KELOMPOK TANI DI DESA SUNGAI BAKAR KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Ahmad Baparki; Marisandy (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
They do not yet know the benefits of the banana tuber, so that a lot of banana tuber waste is often thrown away because no one can process this banana tuber, the community cannot process it because of their lack of knowledge about the benefits of the banana tuber. In fact, this banana tuber has many benefits, one of which is that it can stabilize Blood Sugar. Banana tubers are the lower part of the banana stem which is usually thrown away or not used, whereas the banana tree itself is often found in this location. In order for the banana stem to be useful for the community in improving their health, we make it as a raw material for making chips. so that counseling was carried out on making chips from this banana stem, where the results can be concluded that the people of Sungai Bakar Village or the participants like the chips that are made, they like the taste, color, texture and aroma. In addition, making chips from banana stems is very easy because we only provide banana stems and other flavoring ingredients, these banana stems must be cut thinly so that the spices that have been mixed into the banana stems can be absorbed well so that the chips from these banana stems taste seasoned